HUKUM DAN MASYARAKAT PINGGIRAN (Sekilas Kajian Hukum dan Ekonomi Nelayan Tradisional Saka Tumbang Nusa Kabupaten Pulang Pisau Kalimantan Tengah) - Utsman, Sabian (LP2M IAIN Palangka Raya, 2013)
Law and the rural area people, is a kind of study on law and economy of a community of Saka fishermen at Tumbang Nusa Central Kalimantan. The community of fishermen depends on several numbers of small branch rivers (Saka) as place for looking for fish. Tumbang Nusa is an area in which the community as lower income. This satellite area has not been handled by the government adequately. One of the alternative solutions is the availability of the protection of law which functions effectively. Consequently, the poverty eradication can be done well based on the mandate of the constitution of Republic of Indonesia.